'We Are All Beranselo': Political Subjectivation as an Unintended Consequence of Activist Citizenship. Issue 9 (21st October 2017) - Baća, Bojan
Abstract: Drawing on Jacques Rancière and Engin F. Isin, this essay discusses the success of a citizen-led mobilisation in rural Montenegro that eschewed the country's predominant ethnopolitical identity cleavages by using innovative repertoires of contention. As a result, this grassroots movement unintentionally brought into being a transcendent political subjectivity that was based on civic principles rather than ethnic values. The essay explores how the Beranselo movement embodied a democratic practice radically different from already available institutional practice of politics, in the process transforming the local ethnos into a demos and creating a dynamic of cross-ethnic, civic-minded mobilisation, organisation, and solidarity.